Production and Characterization of Pectic Enzymes of Xanthomonas campestris pv. sesami - Mohammed, Nehal Osman; A. Abdalla, Mai Abdalla; Abdel Rahim, Awad M. (Gezira Journal of Engineering and Applied Sciences; Vol 15 No 1 (2020), 2021)
The bacterium Xanthomonas campestris pv. sesami , is the causal organism of the leaf spot disease (Marad eldum) in sesame plants. Pectic enzymes which were reported to be produced by many plant pathogenic bacteria,  were found to play an important role in pathogenesis. There are three main types of pectic enzymes (Polygalacturonase, PG, Polygalacturonate trans-eliminase PTE and Pectin methylesterase PME). The present study was conducted to investigate the capacity of the bacterium X. campestris pv. sesami ,  to produce the different types of pectic enzymes. A salt medium supplemented with different pectic materials as carbon sources were tested for the production of the enzymes. The produced enzymes were characterized using different selective tests, both the viscosity and reducing group methods were used to measure the enzyme activity. The results showed that no pectin methylestrease (PME) was produced and only the Polygalacturonase trans-eliminase (PTE) was produced by the bacterium. Sodium polypectate and polygalacturonic acid were found as the best substrates giving 26.9 and 19.8 viscosity enzyme units, respectively. The enzyme activity was maximum at the 6 th day (9.3 viscosity units), then the activity was decreasing with further incubation time. The test of the effect of the pH indicated that the  pH optimum of the enzyme activity was at pH 9.0. The effects of different metallic ions to the enzyme activity showed that,= a higher activity was found with Ca ++ which gave 12.2 viscosity    units. When different concentrations of Ca ++ were tested, the maximum activity of the enzyme was found at 50 mg/ ml concentration, which gave 18.0 viscosity units. It could be recommended that the tested bacterium should be investigated for the production of the cellulases and hemi-cellulases which also have a role in the pathogenesis process.